KONFLIK DOMINASI HUBUNGAN INDUSTRIAL ANTARA PT GOJEK INDONESIA DAN BURUH PENGEMUDI OJEK ONLINE TAHUN 2020-2022 - Fathurahman Saleh (2023)
The development of technology and information has also changed the nature of industrial relations, where a term called the 'gig economy' was born. The emergence of Uber in 2009 in the US is considered to be the main reference of how the gig economy works. The trend of economic platforms based on online transportation services such as Uber is also not lost in Indonesia with Gojek as the market disruptor. Gojek's development is increasingly significant, where in 2019 Gojek became the first decacorn in Indonesia, until in 2020-2022 Gojek contributed to economic growth of around 1.6 percent - 2 percent of Indonesia's GDP. Problems arise when Gojek carries a partnership relationship, where various parties see the relationship as a condition of exploitation of their drivers. Various demonstrations have been carried out by various communities of Gojek drivers since 2020-2021, which include demanding regulations on clarity of employment relationships, tariff increases, and a decrease in application fees applied by Gojek. This research tries to analyze why there is a conflict between Gojek and its online ojek drivers in building a partnership relationship that benefits both parties in DKI Jakarta in 2020-2022. This research uses Karl Marx's Conflict theory to explain conflicts related to the phenomenon under study, as well as conflict resolution. The method used in this research is qualitative with explanatory type. The data collected came from interviews and literature studies. The results of this study found that the conflicts that occur in the practice of partnership relations between Gojek and its online ojek drivers are due to the legal vacuum that regulates online transportation services. The legal vacuum is used by Gojek to further dominate and exploit their workers by straddling labor law through the illusion of partnership relationships, thus minimizing the role of the state through relevant ministries, to regulate and mediate work practices that occur due to limited authority. This research recommends that the state, through the involvement of the relevant ministries, should play a firm role in declaring that this relationship is an industrial relationship. As a first step, the relevant Ministries can conduct an official meeting by inviting various stakeholders involved in the practice of this employment relationship in order to create a decent working relationship and the welfare of various parties.